1999
DOI: 10.1007/s007020050161
|View full text |Cite
|
Sign up to set email alerts
|

The activity of the pentose phosphate pathway is increased in response to oxidative stress in Alzheimer's disease

Abstract: In order to assess the integrity of antioxidant enzymes in Alzheimer's disease, the activities of glutathione peroxidase, glutathione reductase and two enzymes of the pentose phosphate pathway (glucose-6-phosphate dehydrogenase and 6-phosphonogluconate dehydrogenase) were determined in three regions of postmortem neocortex of controls and subjects with Alzheimer's disease. The activities of glutathione peroxidase and glutathione reductase were unaffected in Alzheimer's disease. By contrast, there was a selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 45 publications
4
49
1
Order By: Relevance
“…Vulnerable neurons may have increased dicarbonyl products and/or decreased turnover of modified proteins (30). These data fit with increased carbonyl reductase, alcohol dehydrogenase (31), and pentose-phosphate pathway activities (32) in brains from AD patients. In addition, recent data stress the potential importance of glyoxalase I, an enzyme against reactive dicarbonyls, as a risk factor in AD pathogenesis (33).…”
Section: Discussionsupporting
confidence: 62%
“…Vulnerable neurons may have increased dicarbonyl products and/or decreased turnover of modified proteins (30). These data fit with increased carbonyl reductase, alcohol dehydrogenase (31), and pentose-phosphate pathway activities (32) in brains from AD patients. In addition, recent data stress the potential importance of glyoxalase I, an enzyme against reactive dicarbonyls, as a risk factor in AD pathogenesis (33).…”
Section: Discussionsupporting
confidence: 62%
“…Elevation of brain oxidative status of amnesic mice resembled the clinical pathology observed in Alzheimer's disease patients (Palmer, 1999). In this experiment condition, the treatment of p amyloid resulted in a significant decrease of glutathione reductase, glutathione peroxidase and SOD activities.…”
Section: Discussionsupporting
confidence: 56%
“…Aksenov and Markesbery (2001) studied the increased level of oxidative modifications in proteins, lipids, and nucleic acids in the brain of patients with Alzheimer's disease, and they found that the total thiol content was increased by ~ 20% in the patients with Alzheimer in the cerebellum, indicating that the oxidative agents promoted the damage irreversible in the brain. Other investigators have suggested that the synthesis of SH-containing could be increased as a response to oxidative stress in the brain causing disease, and the antioxidant agents could acted preventing this situation (Palmer, 1999). Corwin and Schwarz (1963) studied the properties of α-tocopherol in the presence of reactive free radicals and found that a tocopherol defense mechanism was involved in the protection of essential sulfhydryl groups since the oxidation of tocopherol in the systems containing sulfhydryl groups protected the cells of oxidative damage.…”
Section: Resultsmentioning
confidence: 99%